Clinical Features and Visual Outcome of Uveitis in Japanese Patients Younger than 18 Years. (17th November 2021) - Kitano, Marie; Tanaka, Rie; Kaburaki, Toshikatsu; Nakahara, Hisae; Shirahama, Shintaro; Suzuki, Takafumi; Komae, Keiko; Aihara, Makoto
ABSTRACT: Purpose : To investigate the clinical features and visual outcome of young Japanese patients with uveitis. Methods : Patients younger than 18 years who presented with uveitis at the University of Tokyo Hospital between 2000 and 2018 were retrospectively reviewed. Results : The study comprised 98 patients whose mean age was 12.3 ± 3.8 years. Anterior uveitis was present in 52.0%, panuveitis in 37.8%, and posterior uveitis in 10.2%. The most common diagnosis was juvenile chronic iridocyclitis (JCI) (29.6%) followed by tubulointerstitial nephritis and uveitis syndrome (4.1%) and neuroretinitis (4.1%). Thirty-nine patients received systemic anti-inflammatory treatment. Among all subjects, 56% presented with ocular complications and 20% underwent ocular surgery. Visual acuity of 20/200 or less was observed in 6.2%. The common causes of decreased vision were hypotony, serous retinal detachment, and pupil disorder. Conclusions : JCI was the most common diagnosis. Hypotony, serous retinal detachment, and pupil disorder can lead to visual loss.